Leptospiral lipopolysaccharide mediated Hog1 phosphorylation in Saccharomyces cerevisiae directs activation of autophagy. (December 2022) - Bothammal, Palanisamy; Prasad, Muthu; Muralitharan, Gangatharan; Natarajaseenivasan, Kalimuthusamy
Abstract: Cells have developed a variety of mechanisms to counteract stress to give a specific and adaptive response. Yeast Hog1 is a homolog to mammalian p38, which is a mitogen-activated protein kinase. In this work, we analyze the Hog1 signaling during the induction of leptospiral LPS (100 ng/mL) and the hyperosmotic element NaCl (0.8 M). After the addition of stress elements, the stress-activated protein kinase was phosphorylated within 30 min of exposure and led to the expression of various genes responsible for cell survival. We found that leptospiral lipopolysaccharide mediated Hog1 phosphorylation leads to activation of autophagy-related genes phosphorylation; thereby cells encounter and digest the metabolic waste or organelles for their energy during starvation. And, the wild-type cells accumulate lipid droplets and trigger vacuole calcium release, to maintain cell survival. Loss of Hog1 leads to shrinkage in the cell wall, condensation of the cytoplasmic part, and high-level ROS production. This led to the Hog1 mutant cell death under LPS treatment or stress condition. The phosphorylation of stress-activated kinase during exposure to leptospiral LPS provides insight and knowledge about the organization of cellular metabolic products and cell survival during stress conditions and identifies the pathogenic mechanisms of leptospirosis. Highlights: Leptospiral LPS-mediated Hog1 phosphorylation leads to the activation of autophagy. WT cells accumulate lipid droplets and trigger vacuole calcium release to endure. Loss of Hog1 leads to cell wall shrinkage, condensation of cytoplasm, and ROS. This further explores understanding pathogenesis and developing therapeutics.